Investigating the Structure of Defects in Heterometallic Zeolitic Imidazolate Frameworks ZIF-8(Zn/Cd) and Its Interaction with CO2 Using First-Principle Calculations - Pambudi, Fajar Inggit; Sutarno, Sutarno; Hatmanto, Adhi Dwi; Patmawati, Mita; Utari, Tika Dwi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
Inducing defect in metal-organic frameworks (MOFs) is one of the strategies to modify the structure and properties of this functional material. Defect may occur in a pristine MOF due to missing organic linkers, metal centres and/or other structural behaviours. In this study, the structure of defects in multicomponent MOFs especially heterometallic MOFs of zeolitic imidazolate framework (ZIF-8(Zn/Cd)) was examined to unveil the possible preference defect formation due to missing 2-methylimidazolate (MeIm) and metal centres of Cd2+ and Zn2+. Assuming defect formation due to the reaction between ZIF-8(Zn/Cd) and water, MeIm linker removal is energetically lower than removing metal centres of either Cd2+ or Zn2+. But, the MeIm linker is easier to be removed when it is connected to Cd2+ (Cd-MeIm-Cd) than when it is connected to Zn2+ (Zn-MeIm-Zn). Defect in ZIF-8(Zn/Cd) affects the band gap energy to give slightly lower value than it in pristine ZIF-8(Zn/Cd). Non-covalent interaction (NCI) and interaction region indicator (IRI) analyses were also performed to indicate possible intermolecular forces such as van der Waals and attractive forces present in non-defective and defective ZIF-8(Zn/Cd). The presence of defects in mixed-metal ZIF-8(Zn/Cd) was also tested for its potential use on CO2 adsorption. The interaction energy of CO2 inside defective ZIF-8(Zn/Cd) indicates an exothermic behaviour where CO2 molecule has a preference to be adsorbed inside the framework. This is especially when the capping agents at the defective ZIF-8(Zn/Cd) sites are removed to give open metal sites. This study provides insight how defects in multicomponent MOFs might presence affecting the structural and properties changes. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).